Traveling Wave Solutions of the Conformable Fractional Klein–Gordon Equation With Power Law Nonlinearity - Zhoujin Cui; Tao Lu; Bo Chen (Journal of Mathematics)
This article investigates the construction of new traveling wave solutions for the conformable fractional Klein–Gordon equation, which is a well-known mathematical and physical model that can be used to explain spinless pion and de Broglie waves. In order to accomplish this task, a classic and effective analysis method, namely, the extended tanh–coth method, was utilized. By introducing appropriate transformations, the conformable fractional Klein–Gordon equations are reduced to ordinary differential equations, and then the solutions with hyperbolic function form are obtained. In addition, the effect of fractional parameters on waveform is analyzed by drawing two- and three-dimensional graphics. These results contribute to a deeper understanding of the dynamics of the conformable fractional Klein–Gordon equation. The research in this article also indicates that the extended tanh–coth method is a straightforward and concise technique that has the potential to be applicable to many other conformable fractional partial differential equations that appear in mathematical physics.